Bibliometric Analysis of Islamic Criminal Law Research in the Modern Legal System - Judijanto, Loso; Zuwanda, Zulkham Sadat (Westscience Press, 2025)
This study conducts a bibliometric analysis of Islamic criminal law research within modern legal systems, using data exclusively from the Scopus database and analyzed with VOSviewer. The findings reveal that traditional principles such as hudud and qisas remain central to the discourse, while contemporary themes like human rights, criminal justice, and corruption are gaining prominence. The analysis highlights localized applications, particularly in regions like Aceh, Indonesia, where Sharia law is implemented within a pluralistic legal framework, showcasing both opportunities and challenges. Furthermore, the study underscores ongoing tensions between Islamic jurisprudence and international human rights norms, particularly regarding issues like the death penalty and gender equality. The co-occurrence and collaborative networks indicate an evolving academic landscape that seeks to harmonize traditional Islamic principles with the demands of modern governance and ethical frameworks. This study calls for future interdisciplinary research to address challenges and explore innovative applications of Islamic criminal law, particularly in restorative justice and governance, to ensure its relevance in addressing contemporary societal and legal issues.